2019
DOI: 10.1038/s41598-019-52601-y
|View full text |Cite|
|
Sign up to set email alerts
|

Diversified Floral Resource Plantings Support Bee Communities after Apple Bloom in Commercial Orchards

Abstract: Natural habitats, comprised of various flowering plant species, provide food and nesting resources for pollinator species and other beneficial arthropods. Loss of such habitats in agricultural regions and in other human-modified landscapes could be a factor in recent bee declines. Artificially established floral plantings may offset these losses. A multi-year, season-long field study was conducted to examine how wildflower plantings near commercial apple orchards influenced bee communities. We examined bee abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Overall, areas with a higher diversity of flowers, such as natural habitats, have been shown to also have a higher diversity of bees [73,74]. Incorporating diverse floral plantings in an agricultural landscape could enhance ecosystem services of pollinators and other beneficial insects [75,76], and could support bee communities after the flowering period of main crops [77]. The drop in diversity of solitary bees, as they move farther away from these natural habitats, like woods and prairies, is cause for particular concern, because a higher diversity of bee species can have a positive impact on pollination and plant yield.…”
Section: Floral Diversity Affects Community Dynamics Of Solitary Beesmentioning
confidence: 99%
“…Overall, areas with a higher diversity of flowers, such as natural habitats, have been shown to also have a higher diversity of bees [73,74]. Incorporating diverse floral plantings in an agricultural landscape could enhance ecosystem services of pollinators and other beneficial insects [75,76], and could support bee communities after the flowering period of main crops [77]. The drop in diversity of solitary bees, as they move farther away from these natural habitats, like woods and prairies, is cause for particular concern, because a higher diversity of bee species can have a positive impact on pollination and plant yield.…”
Section: Floral Diversity Affects Community Dynamics Of Solitary Beesmentioning
confidence: 99%
“… Cohen et al (2021) found that pathogen prevalence was diluted instead of amplified for MFC sites that were accompanied by a high non-crop floral abundance. After mass-flowering, the bees that foraged on the MFCs now need to forage on the plants in the surrounding landscape ( González-Varo et al, 2017 ; Heller et al, 2019 ). When the floral abundance is lower here ( Mallinger et al, 2019 ), this may lead to higher floral visitation frequencies and bee densities on these flowers ( González-Varo et al, 2017 ; Benadi et al, 2018 ).…”
Section: The Effect Of Mfcs On Pathogen Transmission Via Flowersmentioning
confidence: 99%
“…Ground‐nesting bee species nest in areas of undisturbed soil, often south facing with low vegetation cover (Antoine & Forrest, 2021 ; Harmon‐Threatt, 2020 ), such potential nesting areas exist in orchards between vegetated alleyways and at the end of trees rows but the extent to which availability of these habitats constrain populations is not known. Floral resources have been introduced into apple orchards as flowering plants in between apple rows (Campbell et al, 2017 ; McKerchar et al, 2020 ) or adjacent to orchards (Carvell et al, 2021 ; Heller et al, 2019 ) to promote pollinators. Such areas are utilized as a pollen and nectar resource by wild pollinators (Carvell et al, 2021 ; Heller et al, 2019 ), but whether these habitats are sufficient to support populations of important taxa with resulting improved crop pollination and how this is affected by existing landscape context is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Floral resources have been introduced into apple orchards as flowering plants in between apple rows (Campbell et al, 2017 ; McKerchar et al, 2020 ) or adjacent to orchards (Carvell et al, 2021 ; Heller et al, 2019 ) to promote pollinators. Such areas are utilized as a pollen and nectar resource by wild pollinators (Carvell et al, 2021 ; Heller et al, 2019 ), but whether these habitats are sufficient to support populations of important taxa with resulting improved crop pollination and how this is affected by existing landscape context is unknown.…”
Section: Introductionmentioning
confidence: 99%